2015
DOI: 10.1039/c5ra06312d
|View full text |Cite
|
Sign up to set email alerts
|

Diopside modified porous polyglycolide scaffolds with improved properties

Abstract: Polyglycolide (PGA) is considered an attractive candidate for bone regeneration because of its good biodegradability as well as biocompatibility. However, its insufficient mechanical strength and inadequate bioactivity limit the applications. In this research, diopside (DIOP) was incorporated into PGA scaffolds for enhancing mechanical and 10 biological properties. The porous scaffolds were fabricated via selective laser sintering (SLS). The effect of DIOP content on the microstructure, mechanical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…36,37 Some inorganic materials have been reported to improve the mechanical and biological properties of bone tissue scaffold. 38,39 The nHA/PA66 porous scaffolds fabricated by a phase inversion method provide a good imitation of natural bone and have been widely used in orthopedics. Xu et al 40 investigated a porous nHA/PA66 scaffold material and showed that three-dimensional pore structures could facilitate cell adhesion, differentiation, and proliferation, and promote fibrovascular and nerve colonization.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Some inorganic materials have been reported to improve the mechanical and biological properties of bone tissue scaffold. 38,39 The nHA/PA66 porous scaffolds fabricated by a phase inversion method provide a good imitation of natural bone and have been widely used in orthopedics. Xu et al 40 investigated a porous nHA/PA66 scaffold material and showed that three-dimensional pore structures could facilitate cell adhesion, differentiation, and proliferation, and promote fibrovascular and nerve colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inclusion of baghdadite enhanced the radiopacity of the composite, as well as the proliferation and osteogenic gene expression (Runx2, osteocalcin, osteopontin) of primary human osteoblasts. Porous PGA scaffolds containing 10 wt % diopside microparticles and fabricated by selective laser sintering exhibited significant increases in compressive strength (10 MPa to 29 MPa), as well as enhanced apatite formation in SBF and reduced acidification effect of PGA degradation which improved the proliferation of MG-63 cells [ 123 ]. Similarly, akermanite powder was found to neutralise the acidic products from polymer degradation when incorporated into PLGA beads to form a drug delivery system [ 124 ].…”
Section: Development Of Dcscs For Broader Clinical Applicationsmentioning
confidence: 99%
“…The porosities of various SiCa and composite scaffolds have been measured using the aforementioned methods: liquid displacement (distilled water), [ 33,49,50,59,67,68,70,71,74,88–120 ] liquid displacement (ethanol), [ 121–125 ] liquid displacement (hexane), [ 126–129 ] liquid displacement (kerosene), [ 130 ] mercury intrusion, [ 131–135 ] gravimetry [ 45,65,110,136–138 ] , μ‐CT, [ 114,116,139–145 ] 1, and SEM [ 75,84,85,143,146–150 ] according to the literature.…”
Section: Methods To Measure the Porosity Of Porous Scaffoldsmentioning
confidence: 99%
“…in which V solid is the solid volume and V total is the total volume of the scaffold. The porosities of various SiCa and composite scaffolds have been measured using the aforementioned methods: liquid displacement (distilled water), [33,49,50,59,67,68,70,71,74, liquid displacement (ethanol), [121][122][123][124][125] liquid displacement (hexane), [126][127][128][129] liquid displacement (kerosene), [130] mercury intrusion, [131][132][133][134][135] gravimetry [45,65,110,[136][137][138] , μ-CT, [114,116,[139][140][141][142][143][144][145] 1, and SEM [75,84,85,143,[146][147][148][149][150] acc...…”
Section: Imaging Techniquesmentioning
confidence: 99%